2022
DOI: 10.3390/jcm11164910
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Roux-en-Y Gastric Bypass on Non-Alcoholic Fatty Liver Disease Fibrosis Assessed by FIB-4 and NFS Scores—An 11.6-Year Follow-Up Study

Abstract: Severe obesity is a strong risk factor for non-alcoholic fatty liver disease (NAFLD). Roux-en-Y gastric bypass (RYGB) surgery effectively induces weight loss, but few studies have described the long-term effects of RYGB on NAFLD-related fibrosis. Data from 220 patients with severe obesity operated by RYGB in Central Norway were analysed. Variables incorporated in NAFLD Fibrosis Score (NFS), Fibrosis-4 (FIB-4) index and anthropometric data were collected before surgery and a mean of 11.6 years postoperatively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Nascimento et al analyzed changes in NAFLD Fibrosis Score before and after bariatric surgery. The NAFLD Fibrosis Score changed from −0.6845 before the surgery to −1.6898 12 months after the procedure (p < 0.0002), indicating an absence of advanced liver fibrosis in any patient 12 months after the surgery [35] In the above-mentioned study, a weak negative correlation between the decrease in NAFLD Fibrosis Score and weight loss parameters (%EWL (r = −0.251, p < 0.0001) and %TWL (r = −0.280, p < 0.0001)) was observed [37]. In our study, a statistically significant decrease in NAFLD Fibrosis Score was also seen.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Nascimento et al analyzed changes in NAFLD Fibrosis Score before and after bariatric surgery. The NAFLD Fibrosis Score changed from −0.6845 before the surgery to −1.6898 12 months after the procedure (p < 0.0002), indicating an absence of advanced liver fibrosis in any patient 12 months after the surgery [35] In the above-mentioned study, a weak negative correlation between the decrease in NAFLD Fibrosis Score and weight loss parameters (%EWL (r = −0.251, p < 0.0001) and %TWL (r = −0.280, p < 0.0001)) was observed [37]. In our study, a statistically significant decrease in NAFLD Fibrosis Score was also seen.…”
Section: Discussionmentioning
confidence: 81%
“…Sandvik et al observed a significant overall shift towards lower risk categories of advanced hepatic fibrosis based on NAFLD Fibrosis Score in 11.6 years of observation (NAFLD Fibrosis Score −1.32 (IQR −2.33; −0.39) vs. −1.71 (IQR −2.49; −0.95, p < 0.001) 11.6 years after surgery). In the above-mentioned study, a weak negative correlation between the decrease in NAFLD Fibrosis Score and weight loss parameters (%EWL (r = −0.251, p < 0.0001) and %TWL (r = −0.280, p < 0.0001)) was observed [ 37 ]. In our study, a statistically significant decrease in NAFLD Fibrosis Score was also seen.…”
Section: Discussionmentioning
confidence: 99%
“…Other nonlipoprotein biomarkers of metabolic syndrome are summarized in Table 2[83–90,91 ▪ ,92,93–100,101 ▪ ,102,103–107].…”
Section: Novel Cardiovascular Risk Factors and Metabolic Syndromementioning
confidence: 99%